Sure! Here's the step-by-step expansion of the expression \((x^2 + x - 2)(x^2 - x - 6)\):
-
Write down the expression: \[ (x^2 + x - 2)(x^2 - x - 6) \]
-
Distribute each term in the first polynomial to each term in the second polynomial:
-
Distributing \(x^2\): \[ x^2 \cdot x^2 = x^4 \] \[ x^2 \cdot (-x) = -x^3 \] \[ x^2 \cdot (-6) = -6x^2 \]
-
Distributing \(x\): \[ x \cdot x^2 = x^3 \] \[ x \cdot (-x) = -x^2 \] \[ x \cdot (-6) = -6x \]
-
Distributing \(-2\): \[ -2 \cdot x^2 = -2x^2 \] \[ -2 \cdot (-x) = 2x \] \[ -2 \cdot (-6) = 12 \]
-
-
Combine all the results: \[ x^4 - x^3 - 6x^2 + x^3 - x^2 - 6x - 2x^2 + 2x + 12 \]
-
Combine like terms:
- From the \(x^3\) terms: \(-x^3 + x^3 = 0\)
- From the \(x^2\) terms: \(-6x^2 - x^2 - 2x^2 = -9x^2\)
- From the \(x\) terms: \(-6x + 2x = -4x\)
- The constant term is \(12\).
-
Write the final expression in standard form: \[ x^4 - 9x^2 - 4x + 12 \]
So the final expanded polynomial in standard form is: \[ \boxed{x^4 - 9x^2 - 4x + 12} \]